Comparative evaluation of venous thromboembolic risk in urologic inpatients using different risk assessment models - Douroumis, Konstantinos; Fragkiadis, Evangelos; Moulavasilis, Napoleon; Stratigopoulou, Panagiota; Adamakis, Ioannis; Anastasiou, Ioannis; Mitropoulos, Dionysios (Canadian Urological Association Journal, 2025)
INTRODUCTIONS: The process for determining thromboprophylaxis decisions in urologic surgery entails assessing the risk of venous thromboembolism (VTE) in comparison to the risk of bleeding. Risk assessment models (RAMs) have been created to systematically calculate an individual’s risk of VTE. In our study, we evaluated the risk of VTE in urologic inpatients using two RAMs specifically designed for urology by the European Association of Urology (EAU) and the American Urological Association (AUA), the Caprini score, and the CHA2DS2-VASc score. METHODS: The study group consisted of 136 inpatients within the urology department. Data from medical records included information on various factors, such as age, gender, and body mass index, as well as personal and family history of the patients. The risk of VTE was determined using the RAMs provided by EAU and AUA, the Caprini score, and the CHA2DS2-VASc score. RESULTS: Chemical prophylaxis was advised for 48 (35.3%) patients according to the EAU model, 47 patients (34.6%) according to the AUA model, 128 (94.1%) patients based on the Caprini score, and 80 (58.8%) patients according to the CHA2DS2-VASc score. Limitations of the study include a small sample size and lack of post-surgery venous thromboembolic events recording. CONCLUSIONS: The VTE RAMs developed by the EAU and AUA provide consistent recommendations for thromboembolism prophylaxis in urologic patients, while the Caprini model’s strict adherence may lead to excessive prophylaxis recommendations. The EAU approach is user-friendly but urologists must judiciously weigh bleeding and VTE risks on an individual basis, ensuring optimal prophylaxis use.